In vitro performance of a pen-type laser fluorescence device and bitewing radiographs for approximal caries detection in permanent and primary teeth - Souza, Juliana Feltrin de; Diniz, Michele Baff; Boldieri, Thalita [UNESP]; Rodrigues, Jonas Almeida; Lussi, Adrian; Cordeiro, Rita de Cássia Loiola [UNESP] (Wolters Kluwer, 2014)
To evaluate the performance of a pen‑type laser fluorescence device (DIAGNOdent 2190; LFpen, KaVo, Germany) and bitewing radiographs (BW) for approximal caries detection in permanent and primary teeth. Materials and Methods: A total of 246 anterior approximal surfaces (102 permanent and 144 primary) were selected. Contact points were simulated using sound teeth. Two examiners assessed all approximal surfaces using LFpen and BW. The teeth were histologically assessed for the reference standard. Optimal cut‑off limits were calculated for LFpen for primary and permanent teeth. Sensitivity, specificity, accuracy and area under the receiver operating characteristic curve (Az) were calculated for D1 (enamel and dentin lesions) and D3 (dentin lesions) thresholds. The reproducibility was assessed by intraclass correlation coefficient (ICC) and Cohen's weighted kappa values. Results: For permanent teeth, the LFpen cut‑off were 0– 27 (sound), 28– 33 (enamel caries) and >33 (dentin caries). For primary teeth, the LFpen cut‑off were 0– 7 (sound), 8– 32 (enamelcaries) and >32 (dentin caries). The LFpen presented higher sensitivity values than BW for primary teeth (0.58 vs. 0.32 at D1 and 0.80 vs. 0.47 at D3) and permanent teeth (0.80 vs. 0.57 at D1 and 0.94 vs. 0.51 at D3). Specificity did not show a significant difference between the methods. Rank correlations with histology were 0.59 and 0.83 (LFpen) and 0.36 and 0.70 (BW) for primary and permanent teeth, respectively, considering all lesions. ICC values for LFpen were 0.71 (inter) and 0.86 (intra) for permanent teeth and 0.94 (inter) and 0.90/0.99 for primary teeth. Kappa values for BW were 0.69 (inter) and 0.68/0.90 (intra) for permanent teeth and 0.64 (inter) and 0.89/0.89 for primary teeth. Conclusion: LFpen presented better reproducibility for primary and permanent teeth and higher accuracy in detecting caries lesions at D1 threshold than BW for permanent teeth. LFpen should be used as an adjunct method for approximal caries detection.
Keywords: Approximal caries; Caries detection; Fluorescence; Radiography